The effect of 12 weeks of chess-based training under time pressure on some electroencephalographic and skill indices in chess players - Vahid Sari-Sarraf; Javad Vakili; Seyed Mahmoud Tabatabaei; Asghar Golizadeh (Shahid Beheshti University, 2024)
Background and Purpose: Playing chess under time pressure is one of the most important challenges faced by chess players during various competitions in the final stages of the game, and it affects the performance of athletes in this field during the competition. Therefore, suggesting the suitable training solutions is considered necessary to improve the performance of athletes in this sport along with its occurrence mechanisms. Therefore, the aim of the current study was to investigate the effect of chess-based training in time pressure on the electroencephalography and skill indices in chess players. Materials and Methods: In a semi-experimental research among chess players with age range of 15-22 yearsin the international level (ELO)of 2000-1400 who had the experience of at least 3 years of chess activity, 28 players voluntarily participated in the study and were randomly allocated into two groups including chess-based training under time pressure and the normal chess training. On the first day of the study, weight, height, body mass index and electroencephalography indices were recorded at rest and during the game under time pressure. The chess-based training group did 12 weeks of special chess training under time pressure,5 sessions per week, 4 hours per session between 16:00 to 20:00. In the sixth and twelfth week of the study protocol, the electroencephalography and skill indices of all subjects were recorded to determine the absolute and relative power of theta and alpha waves and the theta to alpha ratio. The data were analyzed by using a analysis of variance with between group factor, bonferroni post hoc and independent t-test using SPSS22 software at a significance level of P<0.05. Results: Two groups were homogenouse for all measured variables (P>0.05). Six weeks of regular and time-limited exercise resulted in a significant increase in the absolute and relative power index of theta and alpha waves, and the ratio of theta to alpha waves (P<0.05), though no intra-group and inter-group differences were observed for these variables (P>0.05). However, the increase in theta wave and the alpha to theta ratio in the time-limited training group were significantly higher than the normal training group. Conclusion: It could be concluded that time-limited chess-based training may result in positive changes in the cerebral cortex by modulating theta wave activity. Therefore, time-limited chess training can be an effective intervention to improve the brain waves and electrical activity of the cerebral cortex, and that it could potentially improve the brain performance of chess players.